Antioxidant biosensor based on superoxide dismutase from Indonesian microbes immobilized in Indonesian natural zeolite - Dyah Iswantini, Weniarti, Novik Nurhidayat, Zaenal Abidin, Trivadila (Journal of Applied Pharmaceutical Science, 2019)
Common techniques for measuring the capacity and activity of antioxidants are spectrophotometry, fluorescent, liquid and gas chromathography. The antioxidant measurement using spectrophotometry method has its limitation in sample preparation. Therefore, an appropriate method is needed to measure the antioxidant properties in various types of samples, either sample from natural or industrial products. Electrochemical biosensor is a developed alternative method to study the antioxidant capacity because its rapidity, validity and low cost. The immobilization of superoxide dismutase (SOD) extract from Deinococcus radiodurans on a zeolite nanocomposite-modified electrode was studied as an antioxidant biosensor. Cyclic voltammetry was employed to investigate the catalytic behavior of the immobilized-SOD in zeolite nanocomposite. The current response was found to have a direct linear relationship with xanthine (substrate) concentration. The immobilized-SOD activity was optimum at 30°C, pH 9, 137.5 mg zeolite, and 1 μg/ml SOD for pure SOD, and at 30°C, pH 9, 137.5 mg zeolite, and 1,500 μg/ml SOD for D. radiodurans SOD. Dismutation reaction kinetics of superoxide catalyzed by SOD followed the Lineweaver-Burk plot for enzyme kinetics with an immobilized D. radiodurans SOD value smaller than for immobilized pure SOD. In conclusion, a zeolite nanocomposite provided great potential as an immobilization matrix for SOD extract from D. radiodurans for application in antioxidant biosensors.
Keywords: Antioxidant biosensor, superoxide dismutase (SOD), deinococcus radiodurans, zeolite nanocomposite, enzyme kinetics.